(untitled) (Third Sector Social Economic Review, 2021)
The main purpose of this study is to evaluate the relationship between work-life balance and organizational commitment in the context of the global work-life index. In the study, the concepts of work-life balance, OECD Better Life Index and organizational commitment were discussed and the relationship between them was discussed. With the increase in the number of job seekers, organizations can choose what they want. This situation causes employees to experience fear of losing their jobs at any moment. When individuals find a job that can earn their living, they accept the job and continue to work despite the difficult working conditions due to the lack of other options. The amount of time they spend at work limits the time they want to spare for their private lives. Employees who cannot establish a work-life balance become unhappy; their motivation, performance and productivity decrease; as a result, they may leave the organization. Countries that understand the importance of the issue attach importance to the establishment of work-life balance; they develop more inclusive policies for the protection of the family life of the employees, occupational health and safety, flexible working hours, etc. for the employees to spend their time both at work and outside of work. In our study, it was concluded that there are a lot of scientific studies related to the fact that ensuring work-life balance increases organizational commitment.